2021
DOI: 10.1186/s13229-021-00435-9
|View full text |Cite
|
Sign up to set email alerts
|

Tactile cortical responses and association with tactile reactivity in young children on the autism spectrum

Abstract: Background Unusual behavioral reactions to sensory stimuli are frequently reported in individuals on the autism spectrum (AS). Despite the early emergence of sensory features (< age 3) and their potential impact on development and quality of life, little is known about the neural mechanisms underlying sensory reactivity in early childhood autism. Methods Here, we used electroencephalography (EEG) to investigate tactile cortical processing in you… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…Exclusion criteria for the autism group included a known genetic etiology of autism or history of major head trauma including loss of consciousness for >5 min. Children participated in a separate study that included electroencephalography (EEG) described elsewhere ( Espenhahn et al, 2021 ) and were therefore also excluded if they experienced seizures. Co-occurring conditions in the autism group were reported by parents and included attention-deficit/hyperactivity disorder ( N = 5), global developmental delay ( N = 3), and global developmental delay coupled with pre-term birth, <28 weeks gestational age ( N = 1).…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for the autism group included a known genetic etiology of autism or history of major head trauma including loss of consciousness for >5 min. Children participated in a separate study that included electroencephalography (EEG) described elsewhere ( Espenhahn et al, 2021 ) and were therefore also excluded if they experienced seizures. Co-occurring conditions in the autism group were reported by parents and included attention-deficit/hyperactivity disorder ( N = 5), global developmental delay ( N = 3), and global developmental delay coupled with pre-term birth, <28 weeks gestational age ( N = 1).…”
Section: Methodsmentioning
confidence: 99%
“…We now need to address the mechanisms mediating the relationship between somatosensory processing and NDD, taking into account the variety of syndromes. EEG studies in ADHD show increased SEP amplitude (Parush et al, 2007), whereas in ASD they found decreased amplitude and shorter latency (Espenhahn et al, 2021).…”
Section: Somatosensory Impairments In Neurodevelopmental Disordersmentioning
confidence: 96%
“…Recently, Espenhahn et al (2021) found that the N140 response, a component of SEP, had a lower amplitude and shorter latency in children with ASD. As for ADHD, the authors propose that an imbalance between excitation and inhibition in the brain underlies these observations.…”
Section: Somatosensory Impairments In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Moreover, patients with ASD have an aversion to touch, suggesting that a tactile stimulus, albeit weak, is a source of discomfort indicating a potential hypersensitivity to this type of stimulus (Moore, 2015 ; Kaiser et al, 2016 ). This tactile atypia could be explained by an excitation/inhibition imbalance at the level of somatosensory neurons of the DRG (Lipina and Blundell, 2022 ), modification of somatosensation and somatotopic map (Espenhahn et al, 2021 ), or even direct alteration of the somatosensory circuit in patients with ASD (Orefice, 2020 ).…”
Section: Part 2: Importance Of the Oxytocinergic System In The Sensor...mentioning
confidence: 99%